ANTIBACTERIAL ASSAY OF 2’-HYDROXY-4’,6’,4-TRIMETHOXYCHALCONE AND 4-METHOXYCHALCONE AGAINST GRAM POSITIVE AND GRAM NEGATIVE BACTERIA - Wiwit Sepvianti; Serafica Btari Christiyani Kusumaningrum (Jurnal Riset Kesehatan, 2019)
Blood transfusion is currently one of the most important health care treatments. Unfortunately, the prevalence of transfusion reactions caused by the use of blood products is still quite high although blood products have been tested in terms of infectious diseases using 4 parameters, namely hepatitis B, hepatitis C, HIV and syphilis. The results of the analysis of blood products produced by UTD (Blood Transfusion Unit) Surabaya showed bacterial contamination of blood products, starting from normal skin flora to pathogens. Bacterial contamination is also believed to be one of the causes of transfusion reactions. Therefore, it is necessary to make efforts to prevent bacterial contamination of blood products. One of the efforts is to find chemical compounds that have good antibacterial activity. In this study, the antibacterial activity of 2ˈ-hydroxy-4ˈ,6ˈ,4-trimethoxychalcone and 4-methoxychalcone was tested against gram positive and gram negative bacteria. The test method was agar diffusion at various concentrations of chalcone, namely 0.625; 1.25; 2.5 and 5.0%. The results showed that both chalcones had good antibacterial activity against gram-positive and gram-negative bacteria.